Is Apostasy from a Family Possible? The Apostasy from an Alcoholic-Abusive Family as a Variant of (Un)Becoming a Daughter – the Case of Natalia - Urbańska, Sylwia (Qualitative Sociology Review, 2014)
An analysis of the biography of Natalia, a former resident of a Polish children’s home who, at the age of thirteen, voluntarily left her biological, dysfunctional family, aims to address a question which is fundamental, but rarely asked by the sociologists of family. Is it possible to completely quit a relation with one’s family of origin? What identity and biographical consequences does such a decision imply? This article consists of two parts. In the first, theoretical one, I argue that the process of quitting one’s family is a liminal, unstructured status passage, especially, for two categories of actors – adolescents and mothers who decide to pass taking care of children to fathers. I take into account the cultural and institutional basis of the liminal character of their experience. I also explain why, in order to comprehend those difficult instances, I propose using the metaphor of apostasy. The second, empirical part of the article, is devoted to studying the biographical and identity consequences and limitations of the process of apostasy. I analyze them on the basis of Natalia’s autobiography, which provided inspiration for those reflections.